The Use of English Movie for Enhancing Students’ Listening Skills: Teacher’s and Students’ Challenges at Junior High School - Pu'adah Zahra, Rifa Nur; Puji Haryanti , Rahayu; Wahyuni , Sri (Institut Agama Islam Negeri Palopo, 2025)
This study aimed to examine the process of teaching and learning English listening using English movies, identify the challenges encountered by both teachers and students, and determine whether movies can enhance students’ listening skills. This mixed-method research was conducted at Junior High School Tasikmalaya and involved 25 ninth-grade students and one English teacher. Data were collected through document analysis, classroom observations, questionnaires, interviews, and pretest-posttest assessments. The intervention was implemented over four weeks and consisted of three instructional meetings. The findings revealed that the teacher followed the Merdeka Curriculum format and delivered listening instruction in three structured stages: pre-listening, while-listening, and post-listening. Students faced several challenges, including unfamiliar vocabulary, rapid speech, listening anxiety, limited contextual understanding, passive viewing, and minimal exposure to authentic English outside the classroom. The teacher also experienced difficulties related to students' varying proficiency levels, technical and equipment issues, material selection, classroom management, and institutional constraints. The quantitative results indicated a significant improvement in students’ listening skills, with the mean pretest score increasing from 74.24 to 85.00 in the posttest. A paired sample t-test confirmed that this improvement was statistically significant (p < 0.001), demonstrating the effectiveness of English movies in enhancing listening comprehension in the EFL classroom.